2022
DOI: 10.1371/journal.pone.0277814
|View full text |Cite
|
Sign up to set email alerts
|

Self-correction in science: The effect of retraction on the frequency of citations

Abstract: We investigate the citation frequency of retracted scientific papers in science. For the period of five years before and after retraction, we counted the citations to papers in a sample of over 3,000 retracted, and a matched sample of another 3,000 non-retracted papers. Retraction led to a decrease in average annual citation frequency from about 5 before, to 2 citations after retraction. In contrast, for non-retracted control papers the citation counts were 4, and 5, respectively. Put differently, we found onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some eligible articles may be excluded if they meet at least one of the previously defined exclusion criteria. Considering the wide variation in the propagation of retractions, which can lead to retracted articles being cited and considered in studies, it is crucial to practice retractions checking [ 44 ]. Therefore, the eligible studies that are included in the systematic review will be carefully examined using the Scite–an acronym for “Smart citation index”, available online ( https://scite.ai/ ) [ 45 ]–to confirm the validity of the evidence and identify any retraction records [ 41 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some eligible articles may be excluded if they meet at least one of the previously defined exclusion criteria. Considering the wide variation in the propagation of retractions, which can lead to retracted articles being cited and considered in studies, it is crucial to practice retractions checking [ 44 ]. Therefore, the eligible studies that are included in the systematic review will be carefully examined using the Scite–an acronym for “Smart citation index”, available online ( https://scite.ai/ ) [ 45 ]–to confirm the validity of the evidence and identify any retraction records [ 41 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The longer it takes to retract an article allows more time for the research to be cited, spreading the potentially inaccurate information through the literature. Studies show that even after retraction, articles continue to be cited (Al-Ghareeb et al, 2018;De Cassai et al, 2022;Khademizadeh et al, 2023;Kühberger et al, 2022;Wadhwa et al, 2021;Xu et al, 2023). In a study of 840 retracted articles, Khademizadeh et al (2023) found that these publications were cited 5659 times in other research articles, with 1559 (27.5%) of the citations occurring postretraction including being shared on Twitter and other online platforms.…”
Section: Citations Of Retracted Articlesmentioning
confidence: 99%
“…The longer it takes to retract an article allows more time for the research to be cited, spreading the potentially inaccurate information through the literature. Studies show that even after retraction, articles continue to be cited (Al‐Ghareeb et al., 2018; De Cassai et al., 2022; Khademizadeh et al., 2023; Kühberger et al., 2022; Wadhwa et al., 2021; Xu et al., 2023). In a study of 840 retracted articles, Khademizadeh et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By some estimates, research waste is considered to constitute up to 85% of biomedical science output [40]. Even when retracted, these nowphantom publications can remain highly cited in the literature long after their credibility has decayed [41][42][43][44][45][46][47], and citations to retracted publications are rarely critical [48,49].…”
Section: Introductionmentioning
confidence: 99%